2019
DOI: 10.1109/access.2019.2926750
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Two-Way Relaying in Cooperative Power Line Communications

Abstract: This paper studies the performance of a half-duplex (HD) two-way relay (TWR) in power line communication (PLC) over a log-normal fading channel with impulsive noise. We consider the two common relaying protocols: amplify-and-forward (AF) and decode-and-forward (DF). For the DF relaying, we apply physical-layer network coding (PNC) and analog-network coding (ANC) to the PLC TWR. We derive analytic expressions for the average sum capacity and the outage probability of the system. The Monte Carlo simulations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Our results are validated through Monte Carlo simulations averaged over 10 5 channel realizations. To characterize the power line attenuation, we adopt the following parameters: b 0 = 9.4 × 10 −3 , b 1 = 4.2 × 10 −7 , k = 0.7 and f = 30 MHz [9]. The power allocation coefficients of the NOMA transmission are fixed such that a 1 = 0.75 and a 2 = 0.25 [19][20][21].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are validated through Monte Carlo simulations averaged over 10 5 channel realizations. To characterize the power line attenuation, we adopt the following parameters: b 0 = 9.4 × 10 −3 , b 1 = 4.2 × 10 −7 , k = 0.7 and f = 30 MHz [9]. The power allocation coefficients of the NOMA transmission are fixed such that a 1 = 0.75 and a 2 = 0.25 [19][20][21].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The advent of NOMA has enabled research on many conventional techniques, one of which is cooperative relaying [5][6][7][8][9]. In cooperative communications, the relay usually operates with amplify-and-forward (AF) or decode-and-forward (DF) protocols where the advantage of the AF protocol lies in its low processing cost compared to the DF protocol [9]. However, it is shown that the two protocols generally achieve very similar performance when the relay to user link is unreliable [10].…”
Section: Introductionmentioning
confidence: 99%
“…Denote the S 1 to R and S 2 to R channels as h 1 and h 2 , respectively. To simplify the analysis, we assume that the two hops are independent which is a common assumption in the literature [11], [12], [16] and [17]. We assume that the MAC and BC channels are reciprocal in the time division duplex (TDD) operation with negligible pilot overhead [26], [27].…”
Section: A Channel and Noise Modelsmentioning
confidence: 99%
“…In [11], AF two-way relays (TWRs) exploit network coding to facilitate bidirectional communication between two nodes. For AF and DF relaying, the authors of [12] derived closed-form expressions for the ergodic capacity and showed that TWRs can greatly improve the spectral efficiency (SE) compared to one-way relays (OWRs) in PLC networks. Furthermore, multiple-input multiple-out (MIMO) and orthogonal frequency division multiplexing (OFDM) combined with optimal power allocation are shown to achieve the dual goals of robustness against frequency selectivity and high capacity performance [13], [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation